Investigation of Failed Projects or Systems Commissioned and Developed by Some of the Organs of State in South Africa - Tumiso Mokhomole (Journal of Governance and Administrative Reform, 2026)
Abstract This paper investigates failed projects and systems commissioned and developed by selected organs of state in South Africa. Year after year, the Auditor-General of South Africa (AGSA) reports billions of rands in irregular, fruitless, and wasteful expenditure, often with limited consequence management. The study highlights how governance failures, including a lack of oversight, accountability and consequence management within organs of state, are commonly known as the root causes of major project delays and delivery failures in South Africa. The study employed a descriptive qualitative research approach, drawing on purposively selected literature and study materials. Data were collected from secondary sources, including published journals, articles, and reports, as well as primary sources based on the researcher’s lived experience and observations. The data were contextualised and thematically analysed. The findings indicate that some organs of state have commissioned projects and developed systems through external service providers that could have strengthened state capacity and improved public-sector efficiency if they had been properly managed and implemented. However, many of these projects and systems failed to achieve their intended objectives. The study further finds that wasteful expenditure continues unabated in some organs of state due to weak ethical leadership and inadequate consequence management. On an annual basis, AGSA identifies projects and systems implemented by organs of state that fail to achieve their intended purposes and cautions that such irregular, fruitless, and wasteful expenditure could have been avoided if reasonable steps had been taken by technocrats and bureaucrats. Keywords: bureaucrats; consequence management; irregular expenditure; organs of state; projects; technocrats